Correlation between the Expression of Interleukin-6, STAT3, E-Cadherin and N-Cadherin Protein and Invasiveness in Nonfunctional Pituitary Adenomas - Shen, Xiaoxu; Liu, Qi; Xu, Jian; Wang, Yang (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study aimed to investigate the expression of interleukin (IL)-6, signal transducer and activator of transcription 3 (STAT3), epithelial-cadherin (E- cadherin) and neural-cadherin (N-cadherin) proteins in nonfunctional pituitary adenomas, and their correlation with invasiveness.Methods Thirty cases of nonfunctional pituitary adenoma pathological wax specimens were selected from our hospital, including 20 cases of invasive nonfunctional pituitary adenoma (INFPA) and 10 noninvasive nonfunctional pituitary adenomas (NNFPAs). Envision was used to detect IL-6, STAT3, E-cadherin , and N-cadherin in specimens. Statistical methods were used to analyze the correlation between the four proteins and the Knosp classification of nonfunctional pituitary adenomas.Result IL-6 and STAT3 were highly expressed in INFPAs but poorly expressed in NNFPAs. E-cadherin expression in INFPAs was lower than that in NNFPAs. N-cadherin was positive or strongly positive in both groups. Spearman's correlation analysis showed that the expression of IL-6 and STAT3 was positively correlated with Knosp's classification, whereas the expression of E-cadherin was negatively correlated with Knosp classification. Meanwhile, the expression of N-cadherin was not correlated with Knosp's classification.Conclusion The expression of the IL-6, STAT3, E-cadherin proteins were associated nonfunctional pituitary adenomas. However, the expression of N-cadherin was not correlated with nonfunctional pituitary adenomas.
Keywords: pituitary adenoma; interleukin-6; STAT3; E-cadherin